1986
DOI: 10.1016/s0022-5347(17)45924-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Tests for Impotence: A Comparison of Papaverine Injection with the Penile-Brachial Index and Nocturnal Penile Tumescence Monitoring

Abstract: The diagnostic usefulness of nocturnal penile tumescence monitoring, penile-brachial index and intracorporeal injection of papaverine (60 mg. in 20 ml. normal saline) was compared in 43 impotent men. Intracorporeal pressure was measured with a pressure transducer. Based on turgidity, and the time of onset and duration of erection, we classified the impotence as psychogenic/neurogenic (normal vascular competence), mild or severe arteriogenic, or venogenic. The intracorporeal injection of papaverine was useful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 14 publications
1
16
0
4
Order By: Relevance
“…The physiological significance of an ICP-to-BP ratio Ն0.6 in the rat model of penile erection has been previously noted (32) and is further supported by data summarized in Table 4. Similar measurements have been made in humans and reported as the penile-to-brachial index (PBI) (1,8,18,21,23,25,35). In clinical studies, a PBI value of Ͻ0.6 has been used as the cut off below which BP in the penis is considered insufficient to permit penile rigidity.…”
Section: Discussionmentioning
confidence: 87%
“…The physiological significance of an ICP-to-BP ratio Ն0.6 in the rat model of penile erection has been previously noted (32) and is further supported by data summarized in Table 4. Similar measurements have been made in humans and reported as the penile-to-brachial index (PBI) (1,8,18,21,23,25,35). In clinical studies, a PBI value of Ͻ0.6 has been used as the cut off below which BP in the penis is considered insufficient to permit penile rigidity.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, Abber et al [1] reported a remarkably enhanced erection capacity in 10% of their patients after as few as 1-3 trial injections. Robinette and Moffat [17] observed improved sponta neous erections in 11.5% of their patients.…”
Section: Comments To Question 5: Medium-term Effect Of Intracavemosalmentioning
confidence: 95%
“…100 Table 7. Medium-term effect of intracavemosal pharmacother apy Number of patients ( 1 ) In patients with pronounced organic pathogenesis and secondary performance anxiety, therapeutic dose levels are gradually reduced to the point where the organic component can still be overcome under home conditions [20], These patients may show an improve ment in spontaneous erection capacity, yet will not be able to perform intercourse without intracavemosal pharmacotherapy, since their organic threshold is still fairly high.…”
Section: Comments To Question 5: Medium-term Effect Of Intracavemosalmentioning
confidence: 99%
“…One patient inad vertently injected the corpus spongiosum [80], In fact, about 0.5-6% of the patients apply faulty injections [78,79]Cavernitis or infections due to injection have rarely been observed. Authors studying large populations [1,10,22,51,54,78,80] emphasize the absence of infec tions in particular. Sidi and Chen [79] reported one inci dence of cavernositis (0.5% of their patients) as a result of improper injection.…”
Section: Undesired Effectsmentioning
confidence: 99%